A novel approach for the production of DODAB:MO lipoplexes : the influence of temperature on the physicochemical characteristics and cell transfection efficiency - Oliveira, Ana Cristina Norberto Gonçalves (2010)
Cationic liposomes/ DNA complexes (lipoplexes) have been widely used as nano-carriers for animal cell transfection, with the neutral lipid (helper) playing a determinant role for the efficiency of this process due to the formation of non-lammellar intermediates that are akin to membrane fusion process [1]. We have developed a novel formulation containing the cationic agent dioctadecyldimethylammonium bromide (DODAB) and 1-monooleoyl-rac-glycerol (MO) as helper lipid [2]. In previous studies, we have demonstrated a strong dependence of the DNA complexation rate with several structural parameters such as the monoolein content or the DNA/cationic lipid charge ratio (+/-) [3]. The preparation method itself influences the structural properties of the lipoplexes formed as well as their lipofection capacity. This study addressed the effect of preparation temperature (25ºC or 50ºC) on DODAB:MO lipoplexes (molar ratios 4:1 and 2:1) physicochemical properties, as well as on their cell transfection efficiency (TE).